The Use of Xmind Assisted Mind Mapping Technique In Improving Students' Review Writing Skills - Wiarsih, Asih; Muhria, Lanlan (CV. Tripe Konsultan, 2025)
This research is motivated by the lack of students' writing skills in review texts, which is caused by the limited learning strategies that can facilitate critical and systematic thinking processes. The objective of this study is to determine the improvement of students' review writing skills through mind-mapping techniques assisted by Xmind. This study uses the type of Classroom Action Research, which is carried out through actions consisting of 2 cycles, where each cycle has four stages: planning, implementation, observation, and reflection. Research data were obtained using data collection techniques in the form of observation, interviews, assessments, and documentation. The study showed that students' review writing skills with mind-mapping techniques assisted by Xmind had increased significantly. The average score of students' review writing skills increased in each cycle, with an average score of 70.45 for cycle I and 86.81 for cycle II. The cycle I review writing test results showed that 29 students (76.32%) achieved completeness and increased. Thus, the mind mapping technique assisted by Xmind is effectively used as a learning strategy to improve students' review writing skills. Integration of this technique into the writing learning curriculum in higher education is recommended, especially to solve the classic challenges in teaching writing.